Effect of thyme essential oil and Lactococcus lactis CBM21 on the microbiota composition and quality of minimally processed lamb's lettuce. (December 2017) - Siroli, Lorenzo; Patrignani, Francesca; Serrazanetti, Diana I.; Vernocchi, Pamela; Del Chierico, Federica; Russo, Alessandra; Torriani, Sandra; Putignani, Lorenza; Gardini, Fausto; Lanciotti, Rosalba
Abstract: The main aim of this work was to evaluate, at pilot scale in an industrial environment, the effects of the biocontrol agent Lactococcus lactis CBM21 and thyme essential oil compared to chlorine, used in the washing step of fresh-cut lamb's lettuce, on the microbiota and its changes in relation to the time of storage. The modification of the microbial population was studied through pyrosequencing in addition to the traditional plate counts. In addition, the volatile molecule and sensory profiles were evaluated during the storage. The results showed no significant differences in terms of total aerobic mesophilic cell loads in relation to the washing solution adopted. However, the pyrosequencing data permitted to identify the genera and species able to dominate the spoilage associations over storage in relation to the treatment applied. Also, the analyses of the volatile molecule profiles of the samples during storage allowed the identification of specific molecules as markers of the spoilage for each different treatment. The sensory analyses after 3 and 5 days of storage showed the preference of the panelists for samples washed with the combination thyme EO and the biocontrol agent. These samples were preferred for attributes such as flavor, acceptability and overall quality. These results highlighted the effect of the innovative washing solutions on the quality of lettuce through the shift of microbiota towards genera and species with lower potential in decreasing the sensory properties of the product. Abstract : Innovative solutions as an alternative to chlorine to guarantee lamb's lettuce shelf-life. Samples washed with alternative solutions showed a different volatilome than controls. Washing solution affect the quality of lamb's lettuce microbiota. The use of innovative washing solutions affect the composition of spoilage microflora. The sensory analyses highlight the preference by the panelists for innovative products.